Viscosity and Fragility of Selected Glass-forming Chalcogenides - Košťál, Petr; Barták, Jaroslav; Wieduwilt, Torsten; Schmidt, Markus A; Málek, Jiří (Elsevier Science BV, 2022)
Experimental viscosity data for (GeSe2)x(Sb2Se3)100-x melts (x = 50, 60 and 70), obtained by deploying the pressure-assisted melt filling technique (PAMFT), are presented. These data were combined with previously published literature data and fitted over a broad temperature range including glass, undercooled melt, and melt regions by the Mauro-Yue-Ellison-Gupta-Allan (MYEGA) equation. A detailed analysis of different fragility concepts for the studied glass-forming system as well as for other well-known chalcogenide glass formers is presented. On the basis of this extensive analysis, a simple procedure for carrying out viscosity data extrapolation was developed, and the validity of this procedure is discussed.
Viskozita a fragilita vybraných sklotvorných chalkogenidů
Keywords: viscosity; chalcogenides; glass; fragility; viskozita; chalkogenidy; sklo; fragilita